Respiratory Health and Inflammatory Markers—Exposure to Cobalt in the Swedish Hard Metal Industry. Issue 10 (October 2020) - Andersson, Lena; Hedbrant, Alexander; Bryngelsson, Ing-Liss; Persson, Alexander; Johansson, Anders; Ericsson, Annette; Vihlborg, Per; Sjögren, Bengt; Särndahl, Eva; Stockfelt, Leo; Westberg, Håkan
Abstract : Objective: To study the relationship between inhalable dust and cobalt, and respiratory symptoms, lung function, exhaled nitric oxide in expired air, and CC16 in the Swedish hard metal industry. Methods: Personal sampling of inhalable dust and cobalt, and medical examination including blood sampling was performed for 72 workers. Exposure-response relationships were determined using logistic, linear, and mixed-model analysis. Results: The average inhalable dust and cobalt concentrations were 0.079 and 0.0017 mg/m 3, respectively. Statistically significant increased serum levels of CC16 were determined when the high and low cumulative exposures for cobalt were compared. Nonsignificant exposure-response relationships were observed between cross-shift inhalable dust or cobalt exposures and asthma, nose dripping, and bronchitis. Conclusions: Our findings suggest an exposure-response relationship between inhalable cumulative cobalt exposure and CC16 levels in blood, which may reflect an injury or a reparation process in the lungs.